Culture-Based Leadership Development - Tari, Ezra; Koroh, Lanny I.D.; Liufeto, Martin Ch.; Ferdinant Alexander (MultiTech Publisher, 2023)
The pattern of leadership is an important factor in advancing leadership. The degradation of cultural values as a result of modernisation is a barrier to establishing cultural leadership. One of the challenges is the electoral system, as is the reliance on ancestor involvement. For cultural leadership patterns, dynastic and authoritarian leadership are in the forefront. The purpose of this study is to promote the development of cultural leadership. According to the findings, adjustments to leadership style are critical; the development of culture-based leadership also entails the ability to modify leadership styles that are consistent with current cultural norms and rules. Direct and open communication reduces conflict and improves artistic performance. Cultural leaders are carried on over generations, from parents to children, ancestors, and Birthright.